2019
DOI: 10.3390/nu11092184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Germinated Pigmented Rice “Superjami” on the Glucose Level, Antioxidant Defense System, and Bone Metabolism in Menopausal Rat Model

Abstract: Women experience physical, mental, and social changes during menopause. It is important to maintain a healthy diet for effective menopause management. The effect of germinated Superjami, a deep violet colored rice cultivar, on the body weight, glucose level, antioxidant defense system, and bone metabolism in a menopausal rat model was investigated. The animals were randomly divided into three groups and fed with a normal diet (ND), a control diet supplemented with 20% (w/w) non-germinated Superjami flour (NGSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…MFE produced strong and comparable inhibitory effect as the positive control Acarbose with an IC 50 value of 0.70 ± 0.02 mg/mL versus 0.62 ± 0.01mg/mL, respectively, whereas DME had slightly a greater IC 50 value of 1.00 ± 0.02 mg/ mL (Table 2). This finding was in accordance with the reports on the anti-diabetic potential of purple and red rice extracts (Boue et al, 2016) and the enhancing effect on glucose metabolism of germinated pigmented rice (Chung et al, 2019) that suggested the potential of both rice extracts for diabetic patients. However, further studies are required on the effects of the current two rice extracts on glucose metabolism in animals based on clinical trials.…”
Section: In Vitro Studiessupporting
confidence: 93%
“…MFE produced strong and comparable inhibitory effect as the positive control Acarbose with an IC 50 value of 0.70 ± 0.02 mg/mL versus 0.62 ± 0.01mg/mL, respectively, whereas DME had slightly a greater IC 50 value of 1.00 ± 0.02 mg/ mL (Table 2). This finding was in accordance with the reports on the anti-diabetic potential of purple and red rice extracts (Boue et al, 2016) and the enhancing effect on glucose metabolism of germinated pigmented rice (Chung et al, 2019) that suggested the potential of both rice extracts for diabetic patients. However, further studies are required on the effects of the current two rice extracts on glucose metabolism in animals based on clinical trials.…”
Section: In Vitro Studiessupporting
confidence: 93%
“…Some other studies that demonstrated increased SOD levels are research conducted by Soo et al, in which white Sprague-Dawley rats given brown rice for 8 weeks with an average rice intake of 4.4 g/day had higher SOD levels compared to rats given a normal diet with an average difference in SOD levels as much as 2.81 U/ml [32]. Another study conducted by Jung et al demonstrated that there were higher differences in the SOD levels as much as 2.15 U/ml in white Sprague-Dawley rats with an average brown rice intake of 5.2 g/day compared to rats that only consumed white rice for 6 weeks of treatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…Germinated brown rice (GBR) has recently gained popularity in Asia. Germinated rice contains higher quantities of phytochemicals, including GABA, tocopherol, 𝛾-oryzanol, and phenolic compounds than non-germinated rice [ 10 , 11 ]. Germinated grain products have been used as new ingredients in the food industry for improving flavor, taste, mineral absorption, and nutritional value.…”
Section: Introductionmentioning
confidence: 99%